Accommodating student's learning experience through personalized learning style adaptation in computer programming course at Centre for Foundation Studies, IIUM - Idris, Mohd Norhaedir; Bakar, Noor Hasrina; Omar, Mazlinah; Yahya, Norzariyah; Hashim, Nafaizatulnananiah (2012)
Teaching and learning computer programming can be difficult, especially for beginners. Since they are not exposed to any computer programming experience, they may face difficulties if the teaching approaches do not match with their learning styles. Computer programming requires the students to understand logical reasoning and syntax and be able to apply them practically for solving programming problems in nearly all disciplines. Mitra [1] claims that most students feel computer programming is a challenging intellectual exercise. At Centre for Foundation Studies, foundation students encounter difficulties in learning and applying computer programming concepts. Some of them perform better in other science subjects, but find difficulties in grasping the computer programming concepts. In this research, we have used Felder-Solomon Learning Style Inventory to identify C Programming’s students for their preferred learning styles. The result of the survey shows that the Engineering/Computer Science students came from mixed learning styles. Therefore, we have adapted Felder-Solomon’s learning style model, and come out with a model of three hybrid categories. This paper will provide detail suggestions for an online learning system based on a selected topic in C Programming. The system will accommodate the students’ learning style in accordance to the modified Felder-Solomon’s learning style model. As a significant contribution to programming educations, our suggestions may further be adopted for designing personalized learning for other disciplines.